Writing strategy instruction to improve writing performance of Bangladeshi EFL learners : a case study - Karim, Shah Mohammad Sanaul; TG. Nor Rizan TG. Mohamad Maasum,; Hafizah Latif, (Penerbit Universiti Kebangsaan Malaysia, 2018)
Writing is one of the most difficult skills for English as a Foreign Language (EFL) learner to acquire. This skill becomes more difficult for a Bangladeshi EFL learner when he opts to pursue higher studies and is evaluated through the skill of writing in English. This article presents the findings of an experimental case study of writing strategy instruction on the learners’ performance for writing a listing paragraph. The study was conducted on 43 undergraduate level EFL learners majoring in English Language and Literature in International Islamic University Chittagong, Bangladesh. The results demonstrated a positive result for the Bangladeshi EFL learners. The learners are able to write listing paragraphs effectively after the writing strategy instruction. Most of the learners’ written listing paragraphs had more organizational features such as topic sentence, supporting sentences, cohesive devices, concluding signal and concluding sentence. Furthermore, the post-test paragraphs showed fewer errors in terms of subject-verb agreement, use of tense and sentence structure among others. Additionally, the learners scored higher marks based on the evaluation of the raters. The results draw attention to the advantages of writing strategy instruction to write listing paragraph for significant achievements such as maintaining organizational aspects and grammatical correctness.